The Dichotomy Between Legal Certainty and Overlapping Court Rulings - Appe Hutauruk (Jurnal Syntax Admiration, 2023)
Today there are indications of reduced public confidence in the formal law enforcement process through the trial process in the Court. Such conditions are generally due to the public considering the Court no longer a facility as the last bastion for justice seekers, but has a tendency as a means of accommodating the interests of certain parties, especially the interests of the ruler and groups of capital owners such as investors or developers called capitalists. This juridical – sociological phenomenon can be seen in the absence of legal certainty value in Court decisions and the number of Court decisions that are not uniform and even overlap so that they do not have executory value. The domino effect of such a reality, there is a tendency for the community to carry out a secondary coercion system in the form of law enforcement efforts outside the path of the system "formal official law – enforcement system", namely through vigilantism to resolve every legal dispute that occurs.